(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The beam structure is an essential structural element for construction professionals, and most engineers should be familiar with beams. The type of beam structure discussed in this paper is a simple beam structure. Calculating the forces and structural deformations numerically takes longer and require good accuracy. In this increasingly sophisticated era, various kinds of software are available, one of which is SAP2000, which can be used to obtain internal forces and structural deformations quickly and accurately. In this paper, a simple beam structure is modeled and analyzed using SAP2000 software. This paper aims to provide solutions for analyzing structures, especially simple beams. Manual calculations will also validate this paper according to the requirements of static balance. Furthermore, the analysis results using SAP2000 software and manual calculations have been obtained and validated. The analysis results showed that the values obtained did not significantly differ. So it can be concluded that structural analysis with SAP2000 software can be a fast and accurate solution.